A decision support system for a flexible transport system - Dias, Ana (2011)
The provision of traditional public transport services in rural areas have shown to be very inefficient and ineffective. In fact, rural areas are typically characterized by low levels of population density leading to complex demand patterns (low levels and high spatial and temporal dispersion), which in turn leads to low levels of service of conventional transport services (low frequencies, usage of old vehicles, etc). Demand Responsive Transport (DRT) systems have been seen as an effective alternative solution already adopted in several countries. In most cases, however, the services provided by the implementation of the system have revealed to be somewhat inadequate or even unsustainable, and therefore they needed to be either substantially redefined or abandoned. The principal reason for this is the lack of a proper design of the system before undergoing its implementation. The problem is that the viability and sustainability of a DRT system is, in general, highly dependent on the correct tuning of some organizational and functional parameters, namely all those related to the level of flexibility of the services provided. This design work must be carried out before the implementation phase of the system, by using adequate demand and supply models and related methodological approaches to accurately estimate the effects of alternative DRT solutions. Despite the existence of a vast literature concerning DRT systems, there is currently a lack in terms of comprehensive approaches to tackle this problem. In this way, this research proposes an integrated multi-disciplinary framework to support decision-makers in the design and planning of flexible transportation systems.